Resilience and Socio-Ecological Literacy in the territory - Santiago Jiménez, María Evelinda (Economía Sociedad y Territorio, 2018)
Cultural differences, when used as a pretext to violate other’s rights, become a leading motive for extermination, segregation, and racism. However, when these differences become a reason to celebrate; it is possible to create territories for amazement, knowledge, and recognition of one another. When the latter happens, the territories become socio-ecological literacy spaces for those who visit them, while they are also spaces that give rise to processes of resilience among its inhabitants. The objective of this document is to propose reflexive and extramural literacy as a methodological tool for the creation of resilient territories